Imposing Packet Relaying for Mobile Adhoc Networks Using Genetic Algorithm - Theerthagiri, Prasanna V. (International Journal of Sensors Wireless Communications and Control, 2020)
Background: Packet forwarding is an essential network operation in wireless networks to establish communication among wireless devices. In mobile wireless networks, data transmission occurs in the form of packet relaying. In dynamic environmental networks, relaying of the packet is a more complex process and much essential activity. Objective: It requires the co-operation of intermediate nodes in the network. Specifically, in Mobile Adhoc Networks (MANET) it is the most tedious job because of its dynamic topology, limited energy, and other resource constraints. In this paper, a genetic algorithm is adopted for stimulating the packet relaying, such that to assist the co-operation between various nodes in the network. Methods: The genetic algorithm is a metaheuristic process-based evolutionary algorithms. It intends to produce high-quality optimized solutions to any given complex problems. The current research work had carried out an extensive investigation and comparison of existing relevant genetic algorithm based algorithms. Results: The experimental results are evaluated based on the methodology of the genetic algorithm, the number of nodes, robustness, scalability, packet delivery ratio, average energy consumption, and other parameters.
Keywords: Co-operative communication